Contaminação dos recursos hídricos por agrotóxicos: uma análise da precariedade do monitoramento e da inércia no combate - Versolato, Anete (Universidade Federal de São Carlos, 2023)
Excessive pesticide use results in water pollution that is treated for human consumption. Data from the VIGIÁGUA system, available in SISÁGUA, are useful in assisting Health Surveillance agencies in managing health risks associated with treated water. This study aimed to investigate the states that use pesticides the most, such as Mato Grosso, São Paulo, Paraná, Rio Grande do Sul, Goiás, and Minas Gerais, and the action plans or contingency plans to monitor pesticides in water intended for human consumption. The objective was to assess the monitoring of pesticides in water and identify gaps and potential improvements. Data for this exploratory study were collected from sources such as IBAMA, the Ministry of Health (MS), the Capes Periodicals Portal, and Scielo, as well as scientific articles and book chapters. Document analysis were conducted on the IBAMA and MS websites, reviewing spreadsheets with information on pesticides and water quality. The analysis period was from 2014 to 2021, during which pesticide levels in the water of states with the highest consumption were examined. In all states, there is quantification of values above or within the Maximum Permitted Value for the pesticide parameter. Health Surveillance agencies analyze these values individually, as the Ordinance 888/2021 does not establish a maximum limit for the total quantity of compounds in the water, only for each parameter. In some cities, the situation is more critical, as mentioned in the text, and in some states, the number of analyses conducted is insufficient, masking the true situation of the municipality. It was concluded that the actions of Health Surveillance agencies do not adequately consider chronic and multiple exposure to pesticides in water and that there is no uniformity in actions.
Contamination of water resources by pesticides: an analysis of monitoring inadequacy and inertia in combat
Keywords: Água; Agrotóxico; Vigilância em Saúde; Water; Pesticides; Health Surveillance; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL::QUALIDADE DO AR, DAS AGUAS E DO SOLO; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA